The United States at the End of the “American Century”: The Rule of Law or Enlightened Absolutism? - Gerhard Casper (Washington University Journal of Law & Policy, 2000)
How satisfied should we be with the accomplishments of our legal system? Is the United States’ legal system something we should want to export?
Keywords: Rule of law; History; Political science; United States